Quantum dots for a high-throughput Pfu polymerase based multi-round polymerase chain reaction (PCR). Issue 5 (13th February 2018) - Sang, Fuming; Zhang, Zhizhou; Yuan, Lin; Liu, Deli
Abstract : We developed a Pfu polymerase based multi-round PCR technique assisted by quantum dots (QDs). Abstract : Multi-round PCR is an important technique for obtaining enough target DNA from rare DNA resources, and is commonly used in many fields including forensic science, ancient DNA analysis and cancer research. However, multi-round PCR is often aborted, largely due to the accumulation of non-specific amplification during repeated amplifications. Here, we developed a Pfu polymerase based multi-round PCR technique assisted by quantum dots (QDs). Different PCR assays, DNA polymerases (Pfu and Taq), DNA sizes and GC amounts were compared in this study. In the presence of QDs, PCR specificity could be retained even in the ninth-round amplification. Moreover, the longer and more complex the targets were, the earlier the abortion happened in multi-round PCR. However, no obvious enhancement of specificity was found in multi-round PCR using Taq DNA polymerase. Significantly, the fidelity of Pfu polymerase based multi-round PCR was not sacrificed in the presence of QDs. Besides, pre-incubation at 50 °C for an hour had no impact on multi-round PCR performance, which further authenticated the hot start effect of QDs modulated in multi-round PCR. The findings of this study demonstrated that a cost-effective and promising multi-round PCR technique for large-scale and high-throughput sample analysis could be established with high specificity, sensibility and accuracy.